Nazi camps and their neighbouring communities history, memory, and memorialization - Whatmore-Thomson, Helen J. (Oxford scholarship online, 2020)
Nazi concentration camps were built close to local populations all across Europe. These nearby communities were involved with the camps in a myriad of ways, and after the war, they continued to interact with camp legacies. This study examines locality-camp relationships and how these played out during and after the war